Konflik Internal Remaja dalam Konteks Long-Distance Parenting: Implikasi bagi Praktik Bimbingan Konseling - Zahwa, Dewi Silvia; Nisa,, Zuhrotun; Fitriana, Ani Qotuz Zuhro (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2025)
Differences in perspectives between parents and adolescents regarding future plans often trigger internal conflict, especially when parents insist on continued formal education while adolescents have different aspirations, such as working or getting married. This conflict reflects a tension between external expectations and personal autonomy, which can impact adolescents' psychological well-being and decision-making capacity. This study is significant because such issues are rarely explored in depth despite being common in real-life situations. Using a qualitative case study approach, the research involved 12th-grade high school students who experienced pressure when deciding on post-graduation plans. Data were collected through in-depth interviews, observations, and documentation. The findings reveal that adolescents often face emotional distress, identity confusion, and a sense of powerlessness when forced to follow parental expectations. Their coping strategies ranged from passive compliance to active negotiation. This study highlights the need for open dialogue between parents and children, as well as the crucial role of school counselors in helping adolescents recognize their potential and make meaningful life decisions.